Identity Crisis in Romesh Gunesekera’s Reef: A Psychological Perspective - Rizwan, Muhammad; Kennedy Jeevaretnam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
A sense of uniqueness naturally exists in every human, termed as ‘identity.’ It begins to form from childhood and develops throughout life with different dimensions in psychological, social and cultural perspectives. The process of identity formation can be affected, leading to ‘identity crisis.’ Internal and external forces and pressures contribute to this crisis. Like real people, the characters of novels written in different periods encounter the aspects of identity crisis. Exploring how characters in novels react to resolve issues of identity crisis can offer valuable lessons for real-life individuals facing similar challenges. Almost all novelists in world literature expose different kinds of identity crises. Their exposure may differ from country to country, gender to gender, and culture to culture even within one country. This study aims to examine the different features of identity crisis experienced by the characters and the mechanisms employed by them to navigate these crises, as depicted in the novel Reef by the Man Booker Prize-shortlisted novelist Romesh Gunesekera. It employs qualitative textual analysis using psychological and identity theories as the analytical framework.